Turkish Postmodernism through the “Second Wave” Paradigm: The Example of Creative Work by Hasan Ali Toptaş and Perihan Mağden - Grebenshcikova, Kseniya V.; Nigmatullina, Alsu M. (Journal of History Culture and Art Research, 2017)
This paper describes the aspects of Turkish postmodernism of the "second wave", which is justified by an insignificant number of theoretical works and inadequate elaboration of studies concerning the representatives of Turkish postmodernism "second wave". The exception is represented by the works of Russian turkologists M.M. Repenkova and O.V. Kareva, who consider the features of the postmodern paradigm in their studies within the novelistics of the leading representatives of the Turkish postmodernism "second wave". The representatives of the "second wave" (Hasan Ali Toptaş, İhsan Oktay Anar, Perihan Mağden, Kürşat Başar, etc.) were not the object of close research before, and therefore the consideration of their creativity as the next stage in the development of Turkish postmodernism is relevant. The "second wave" of postmodernism is characterized by the appeal to the literature of symbolic modeling in 1990s. During this period, the literature of postmodernism develops into a powerful trend, which becomes the predominant trend of the cultural life of Turkey in 2000s. It is worth noting that, if in the postmodern prose of 1980s was marked by the dominance of "lyrical stream", then in 1990s and 2000s the dominant trend was represented by narrative modification. Hasan Ali Toptaş, known for his mastery of language use, is regarded as one of the main representatives of the second wave of postmodern literature.